The Identity of Political Islam in a Democratic Regime: The Ideology of the Prosperious Justice Party (PKS), Indonesia and the Justice and Development Party (AKP), Turkey - Fuad, Ahmad Nur; Syafaq, Hammis; Rofhani, Rofhani (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2026)
This study focuses on the identity and ideological orientation of two Islamic political parties, as well as their steps towards ideological moderation and specific electoral strategies within the political landscapes of two different countries. This is a library-based research that explores the identity of political Islam ideology in secular democracies, utilizing a combination of historical and political approaches. The sources include literature and writings about political Islam groups in Indonesia and Turkey, specifically PKS and AKP, derived from reputable books and scholarly articles. The study concludes that both PKS and AKP are moderate in ideology and politics. PKS, especially in post-New Order, transformed through moderation and inclusion, maintaining its Islamist identity while forming coalitions with nationalist parties for survival. Meanwhile, AKP combines moderate Islamism with conservative democracy, though Erdogan’s dominant leadership tends toward authoritarianism.